"Mad" technology: changes in the national innovation systems of Japan, Korea and Taiwan. (24th February 2004) - Oh, Ingyu; Park, Hun-Joon; Park, Sunghoon
This paper raises two questions about the overall national innovation systems (NIS) of Japan, Korea and Taiwan: what has distinguished the three countries in terms of their NIS in the past; and why are the changes that are taking place now making the NIS in these countries relatively similar to each other? At present, the NIS of each country is becoming more privatised and flexible than in the pre-financial crisis period. We argue that this assimilation is due to the free flowing technologies readily available in the international markets, either real or virtual. "Mad" technology augurs significant shifts in the NIS of these three countries, notably a move from a manufacturing-based NIS with a high level of protection, piracy and stability, to a venture-based NIS with high levels of flexibility, risk taking and technological innovation.